Technology-Driven Community Waste Management Model: Transforming Organic Waste into Renewable Energy - Junus, Mochammad; Mustain, Asalil; Putra, Indra Lukmana; Afrizal, Daffa; Bintang, Zahril; Rizky, M Aldo; Akbar, Fillah; Herdiana (Jurnal Pengabdian Masyarakat, 2025)
Purpose: This study addresses the challenge of ineffective organic waste management in Indonesia by developing a technology-driven, community-based model. Method: An integrated system was implemented at an Integrated Waste Processing Facility (TPST), featuring an automatic sorter using color, infrared, and weight sensors, combined with an anaerobic bioreactor for biogas production. The process was monitored through an IoT platform for real-time control. Practical Applications: The system improved sorting efficiency and reduced processing time, while community training increased household waste segregation participation from 15% to 48%. Conclusion: The model achieved 92% sorting accuracy and produced an average of 22 m³ of biogas per ton of waste, demonstrating that combining automation with social empowerment creates an effective and replicable solution for sustainable waste management and renewable energy transition.